Exploring the structural variability in developing wheat grains using autofluorescence multispectral imaging at the macroscopic scale - Chateigner-Boutin, Anne-Laure; Guillon, Fabienne; Devaux, Marie-Françoise (Frontiers in Plant Science, 2025)
IntroductionThe wheat grain undergoes major changes in dimensions, shape and composition during its development, and the outer tissues of the grain contribute to these modifications. Exploring the spatial and temporal variability in the developing wheat grain contributes to our knowledge of cereal grain development which is necessary to improve traits of interest such as grain weight and shape.MethodsA series of 40 autofluorescence multispectral images was acquired for whole grain sections at four developmental stages. The images were analyzed using principal component analysis of large image series (large PCA). This chemometric method enables the quantification of the variability, its localization, highlighting the associated spectral characteristics and their attribution to chemical compounds.ResultsRegional and temporal heterogeneity was revealed. Among the new information, the lignification of cell walls in pericarp tissues first appeared patchy and later homogeneous. Polar differences have been found in aleurone cell walls for phenolic compounds.DiscussionThis work demonstrates that multispectral autofluorescence analysis of plant organ sections combined with large PCA is a powerful tool for studying the relationship between tissue chemical composition, its variability and the internal structure of organs at the macroscopic scale.